2013
DOI: 10.1159/000348542
|View full text |Cite
|
Sign up to set email alerts
|

Performing Radical Cystectomy and Urinary Diversion in Regional Anesthesia: Potential Risk Reduction in the Treatment of Bladder Cancer

Abstract: Objective: To assess the feasibility and performance of radical cystectomy with urinary diversion using exclusively regional anesthesia (i.e. combined spinal thoracic epidural anesthesia, CSTEA), avoiding the adverse effects of general anesthesia. Materials and Methods: In our hospital, radical cystectomy with extended pelvic and iliac lymphadenectomy and urinary diversion was performed on 28 patients using CSTEA without applying general anesthesia, in 2011 and 2012. Under maintained spontaneous breathing, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The PubMed search for publications reporting on the same procedure identified three further studies. 8 10 Two of these studies reported on series including more than 10 individuals. 8 , 9 Of these, Friedrich-Freksa et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PubMed search for publications reporting on the same procedure identified three further studies. 8 10 Two of these studies reported on series including more than 10 individuals. 8 , 9 Of these, Friedrich-Freksa et al.…”
Section: Resultsmentioning
confidence: 99%
“… 8 10 Two of these studies reported on series including more than 10 individuals. 8 , 9 Of these, Friedrich-Freksa et al. 8 reported on a prospective series, whereas Tzortzis et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations